Implementasi Audio Description sebagai Bentuk Inklusi kepada Disabilitas Netra dalam Film Dokumenter Tiada Batas - Siti Suhada; Wahdiansyah - (Rekam, 2026)
Implementation of Audio Description to Promote Inclusion  for the Visually Impaired  Audiences in the Documentary Film Tiada Batas. This study is motivated by the limited implementation of audio description in Indonesian documentary films, particularly in the context of media accessibility for visually impaired audiences. While previous studies have examined audio description within the field of audiovisual translation, its application in practice-based documentary production remains limited and underexplored. This research aims to examine the implementation of audio description as an inclusive strategy and to analyze its impact on audience comprehension. The study adopts a practice-based research approach combined with qualitative methods. Data were collected through semi-structured interviews with visually impaired participants. The findings indicate that the implementation of audio description significantly enhances audience understanding of visual elements while also strengthening the construction of narrative imagination. These results demonstrate that audio description functions not only as a technical accessibility tool but also as a narrative strategy that enriches the viewing experience in documentary filmmaking. This study contributes to the development of media accessibility discourse, particularly in the context of inclusive documentary film production in Indonesia.